Pelatihan Pembuatan Teh Herbal di Geneng, Jambakan, Bayat, Klaten - Nurul Hidayati; Hendra Budiman; Nuha Zahrona; Nanda Rahmawati; Novika Nur Gaheny; Nindita Krisnawati; Lisa Hariyanti; Nabiha Izzatul (WASATHON Jurnal Pengabdian Masyarakat, 2024)
This training made herbal tea preparations as traditional medicinal preparations formulated as a treatment for hypertension, gout, and ulcers and innovated into tea bags. Herbal tea bags have several advantages including practicality and ease of use. The training of making herbal tea aims to make Geneng Village independent of herbal tea in the sense that it is independent of the source of raw materials, independent of how to process it, and independent of how to use it, helping the community to carry out herbal tea self-medication in the Geneng Hamlet area, Jambakan, Bayat, providing counseling about herbal tea, how to process traditional medicine, and how to use it, providing learning and practice of making herbal tea, improving the quality of health through herbal tea development education related to the cultivation of herbal medicinal plants. This training began with a preliminary study in Dukuh Geneng, preparation of proposals, preparation of tools and materials, implementation of training, monitoring success, and preparation of the final report. The methods used in this training were lectures (delivery of educational materials), discussions (questions and answers), and training (practice making herbal tea). The results obtained from this training were that the majority of herbal tea making training participants could practice making herbal tea well.